Decompressive Bone Flap Replacement (Decompressive Cranioplasty): A Novel Technique for Intracranial Hypertension—Initial Experience and Outcome - Ye, Junhua; Liang, Mingli; Qiu, Qizheng; Zhang, Wenbo; Ye, Min (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Intracranial hypertension is a life-threatening condition that can be treated by decompressive craniectomy (DC), which involves removing a part of the skull and intracranial lesions. However, DC has many complications and requires a second surgery to repair the skull. Decompressive bone flap replacement (DBFR) or decompressive cranioplasty is a novel technique that replaces the bone flap with a titanium mesh, providing both decompression and skull integrity.Methods The materials and methods of DBFR are described in detail. A three-dimensional titanium mesh is fabricated based on the computed tomography (CT) data of previous DC patients. An appropriate titanium mesh is selected based on the preoperative and intraoperative assessments. After removing the intracranial lesions, the titanium mesh is fixed over the bone window.Results We successfully performed DBFR in three emergent cases. The postoperative CT scan showed adequate decompression in all cases. No reoperation for skull repair was needed, and there were no surgical complications. The cosmetic outcome was excellent. There were no relevant complications in the operative area.Conclusions DBFR may be a safe and effective alternative to DC in a specific subgroup of patients, in whom complete removal of the bone flap is feasible. DBFR can reduce intracranial pressure while maintaining the integrity of the skull cavity, eliminating the need for additional surgery for skull repair. Possible improvements for DBFR in the future are suggested, such as using a greater curvature of the titanium mesh or a modified DBFR with a hinged titanium mesh.
Keywords: decompressive bone flap replacement; decompressive cranioplasty; intracranial hypertension